RADIATIVE AND LEPTONIC DECAY OF MESONS - Zhaugasheva, S.A.; Nurbakova, G.S.; Saidullaeva, G. (Хабаршы. Физика сериясы, 2018)
Radiative and leptonic decay mesons consisting from heavy and light quarks are considered. The transition matrix element from an initial state to a final state taking into account the relativistic corrections are determined. The widths of Е1 transitions and leptonic decays of mesons consisting of light and heavy quarks is defined.